2020
DOI: 10.1177/1098612x19900408
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent thoracic pathology identified with radiology in hyperthyroid cats referred for radioiodine therapy

Abstract: Objectives Radioiodine (RAI) treatment for hyperthyroidism is becoming increasingly available in the UK. Pretreatment assessment is commonly performed, as patient handling is limited once RAI has been administered. The aims of this study were to determine the prevalence of thoracic pathology using thoracic radiography in hyperthyroid cats referred for RAI treatment and to determine the value of this technique pretreatment. Methods The hospital databases were searched for hyperthyroid cats referred for RAI trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The only pulmonary pattern found in hyperthyroid cats in this study was a bronchial pattern, as opposed to a previous study, which found bronchial, bronchointerstitial, interstitial, alveolar, nodular, vascular and mixed patterns in hyperthyroid cats presenting for radio iodine therapy. 4 In addition, only 13/52 (25%) of the hyperthyroid cats in this study had an abnormal pulmonary pattern, whereas 115/194 (59%) of the cats in the previous study had an abnormal pulmonary pattern. However, when excluding other types of pulmonary patterns, the prevalence of a bronchial pattern was similar between our study (n = 13/52; 25%) and the previous study (n = 40/194; 21%).…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…The only pulmonary pattern found in hyperthyroid cats in this study was a bronchial pattern, as opposed to a previous study, which found bronchial, bronchointerstitial, interstitial, alveolar, nodular, vascular and mixed patterns in hyperthyroid cats presenting for radio iodine therapy. 4 In addition, only 13/52 (25%) of the hyperthyroid cats in this study had an abnormal pulmonary pattern, whereas 115/194 (59%) of the cats in the previous study had an abnormal pulmonary pattern. However, when excluding other types of pulmonary patterns, the prevalence of a bronchial pattern was similar between our study (n = 13/52; 25%) and the previous study (n = 40/194; 21%).…”
Section: Discussionmentioning
confidence: 47%
“…With the addition of subjective evaluation of cardiomegaly, and testing for inter-and intra-observer agreement for such subjective measures, a significant association may be found between hyperthyroidism and cardiomegaly, as previously reported. 3,4,14 The results of this study indicate that pulmonary hyperinflation is not identified more commonly in hyperthyroid cats than non-hyperthyroid cats. As there is no significant association between hyperthyroidism and pulmonary hyperinflation, hyperthyroidism is an unlikely differential for radiographic pulmonary hyperinflation.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations